Studi Kebutuhan Instalasi Pengolahan Air Limbah (Ipal) Tempat Pembuangan Akhir Sampah Dengan Geomembrane Kota Bengkulu - Oscar Hidayat; Tri Sefrus; Meilani Belladona (MAJALAH TEKNIK SIMES, 2021)
Based data from Bengkulu Environmental centre in 2019, it is known that the volume of waste for Bengkulu city residents per day reaches 373.07 m3/day. The amount of water that enters the Air Sebakul TPA causes leachate to collect quickly and then moves to dissolve into the ground. The absence of waste water treatment plant at this landfill causes contamination of surface water and ground water. Especially when it rains, the leachate will flow into the drainage channels of residents around the TPA which causes an unpleasant odor. The purpose of this research ia to determine the ned for WWTP (waste water treatment plant) at the Air Sebakul TPA Bengkulu by using geomembrane layer. The method of the study uses a survey method with forecasting using geometric formulas and mononobe while the data validation test uses a tracking signal approach.The results of this study show that the prediction of the Bengkulu city waste heap and leachate discharge for the next five years is 792.746,35 (m3/year) or 9.972 m3/day. Based on the current land capacity which has an area of + 30.000 m2, The air Sebakul TPA is declared capable of accommodating waste for the next years. While the planning for the next ten years with waste generation reaching 1.728.810, 26 (m3)/year is declared unable to accommodate waste.Therefore, a large-scale land expansion is needed from the existing land availability, as well as a larger IPAL storage capacity.